Principles of the New Ecosystem Formation: Multicultural Space - Kharlanov A. S., Strygina S. V., Trubnikova N. V., Chursina K. A., Sitokhova T. E., Khachirov K. A., Kotilko V. V., Ermakov D. N., Vragova E. V., Murzakulov N. A., Yslamov M. M., Shpak A. S., Olivio A., Semeno A. A., Danilchenko S. L., Platonova I. I., Sudakov O. V., Sudakov D. V., Danilchenko S. L., Smirnova S. P. (Principles of the New Ecosystem Formation: Multicultural Space, 2022)
the chapter of the monograph is devoted to the consideration of the prospects for building educational ecosystems for people with disabilities. New requirements for the system of education of persons with disabilities in modern conditions have been determined, directions for the development of digitalization in education have been identified. The author analyzes new reserves in the training of people with disabilities to understand this historical time, systemic activity in the context of increased interaction, inclusion, new competencies, professional behavior and responsibility in the learning process. The chapter considers the integration processes in the education of persons with disabilities, the implementation of inclusive educational programs, including remotely, the opportunities and prospects for them to receive higher statuses, and a general improvement in their quality of life.
Keywords: инклюзивное образование; инклюзия; цифровизация; люди с инвалидностью; inclusive education; digitalization; inclusion; образовательная экосистема; информационная доступность образования; educational ecosystem; people with disabilities; information accessibility of education